Pelacakan Lokasi Tinggalan Hindu - Buddha Berdasarkan ROD 1914 Dan Pendekatan SIG di Wilayah Magelang - Ari Mukti Wardoyo Adi (Balai Arkeologi Yogyakarta, 2020)
Java was once the center of Hindu and Buddhist culture around the 4th until the 15th century AD. The number of archaeological remains from this period is infinite, both monumental remains such as temples and petirtaan (water shrines/ temple), and other remains such as yoni, linga, and statues. These remains are registered systematically by the Dutch East Indies government through its Archaeological Service (Oudheidkundig Dienst). unfortunately, most of them cannot be identified for their exact present locations. Some of the remains were later discovered unexpectedly at the time of construction or agricultural work activities. Therefore, this study seeks to investigate the locations of archaeological remains as reported by the Dutch Archaeological Service in the region of Magelang using the Geographic Information System (GIS) approach. This study suggests that, during the period of the Dutch East Indies, Magelang region has a very high density of Hindu-Buddhist archaeological remains. The result of this study can be used for further surveys, re-inventory, as well as protection and preservation efforts.